2018
DOI: 10.1183/16000617.0102-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests as outcomes for systemic sclerosis interstitial lung disease

Abstract: Interstitial lung disease (ILD) is the leading cause of morbidity and mortality in systemic sclerosis (SSc). We performed a systematic review to characterise the use and validation of pulmonary function tests (PFTs) as surrogate markers for systemic sclerosis-associated interstitial lung disease (SSc-ILD) progression.Five electronic databases were searched to identify all relevant studies. Included studies either used at least one PFT measure as a longitudinal outcome for SSc-ILD progression ( outcome studies)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 173 publications
1
51
0
Order By: Relevance
“…In reality, at the moment, the treatment of ILD-SSc has produced conflicting results, despite the large number of compounds studied [30]. The lack of significant results in clinical trials can be explained by the absence of validated primary outcomes (e.g., PFTs parameters [31]), but a role could be played by the frequent absence of stratification according to the HRCT pattern. A prevalent GGO involvement could be an expression of DA and it might benefit from aggressive immunosuppression, whereas in the presence of HC areas or even a UIP pattern, this treatment could be detrimental, as reported for idiopathic pulmonary fibrosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…In reality, at the moment, the treatment of ILD-SSc has produced conflicting results, despite the large number of compounds studied [30]. The lack of significant results in clinical trials can be explained by the absence of validated primary outcomes (e.g., PFTs parameters [31]), but a role could be played by the frequent absence of stratification according to the HRCT pattern. A prevalent GGO involvement could be an expression of DA and it might benefit from aggressive immunosuppression, whereas in the presence of HC areas or even a UIP pattern, this treatment could be detrimental, as reported for idiopathic pulmonary fibrosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new drugsrituximab [45,46], mycophenolate [47], their combination [48], and nintedanib [49] have the potential to provide an effective therapy for ILD. These therapies have been shown to improve parameters of pulmonary function that are related to prognosis, such as DLCO, DLCO/ FVC and TLC [45,50,51], but to date no study has actually demonstrated improved survival in patients treated with immunosuppressive agents. Hence, there is a need for new parameters that better predict long time survival under immunosuppression [52].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneity of the disease, SSc represents a major clinical challenge for both physicians and patients [2]. In addition to disfiguring skin involvement, SSc can affect multiple organ systems, including the lungs [3]. The clinical course is variable, but organ manifestations frequently occur early in the disease [4].…”
Section: Introductionmentioning
confidence: 99%